Inspection of bottles crates in the beer industry through computer vision - Campos, Mário (2010)
This article presents a system developed for the industry of bottling beer. The system has to perform the inspection of various items in the final stage, meaning after the production phase where the bottles are already in the crate. The items to inspect are the following: whether the crate is correct (with the correct color), whether the crate is broken, whether the crate is fully populated, i.e., all bottles are present, to check for bottles without caps and whether the capsule is the correct one. The work uses techniques of computer vision for these verifications and also principal components analysis (PCAs) for the recognition of the capsules. This system is currently installed in the assembly line and the results indicate high efficiency and confidence in the obtained solution.